The Effect of Animation Media in Discovery Learning Model on Students’ Representation Ability on Chemical Equilibrium Materials - Azzajjad, Muhammad Fath; Ahmar, Dewi Satria; Syahrir, Muh. (Journal of Applied Science, Engineering, Technology, and Education, 2020)
This study aimed to determine the effect of animation media in discovery learning model on the students’ representation ability on chemical equilibrium materials. This study was an experimental study using post-test only group design. The study population consisted of 6 classes or 127 students. The sampling technique was done by using purposive random sampling, and 2 classes were chosen consisting of 53 students. Data were collected using a representation ability test which included macroscopic ability, submicroscopic ability, and symbolic ability. By using the inferential analysis of the Mann Whitney test, it was obtained that the significance value for the macroscopic ability was 0.003, the submicroscopic ability was 0,000 and the symbolic ability was 0.041. The significance value is smaller than α = 0.05. Referring to that, it can be seen that there is an influence of animation media in discovery learning model on the students’ representation ability on chemical equilibrium material.